An Illustration of some methods to detect faults in geared systems using a simple model of two meshed gears - de Almeida, Fabrício Cesar Lobato [UNESP]; Carlos Gonçalves, Aparecido [UNESP]; Brennan, Michael John [UNESP]; Paschoalini, Amarildo T. [UNESP]; Arato Junior, A. [UNESP]; Silva, Erickson F.M. (Springer Nature, 2017)
Gears are the components in many mechanical systems that are likely to develop faults due to their dynamic characteristics, such as the cyclic loading applied to the meshing teeth. The main faults in gears are pitting and scuffing, where the tooth profile (involute) is heavily affected, and hence, signal processing techniques have been developed to aid in the detection of gear faults in their early stages. It is already known that the dynamic behaviour of a mechanical system changes when its characteristics are affected (such as in the presence of a fault), and as a result, the vibration of such a system can be used to detect a fault in its early stage. To investigate and develop techniques based on vibration analysis, a physical understanding of the system involving meshing gears is required. In this chapter, a model is introduced that can be used for simulating vibration data of toothed meshing gears. The data generated by the simulations is then used to investigate some classic techniques used in gear fault detection problems.
Keywords: Detection; Fault; Gears; Simulation